A Prospective Study Assessing Complication Rates and Patient-Reported Outcomes in Breast Reconstructions Using a Novel, Deep Dermal Human Acellular Dermal Matrix. Issue 12 (December 2015) - Vu, Michael M.; De Oliveira, Gildasio S.; Mayer, Kristen E.; Blough, Jordan T.; Kim, John Y. S.
Abstract : Background: The value proposition of an acellular dermal matrix (ADM) taken from the deep dermis is that the allograft may be more porous, allowing for enhanced integration and revascularization. In turn, this characteristic may attenuate complications related to foreign body reactions, seromas, and infection. However, this is juxtaposed against the potential loss of allograft structural integrity, with subsequent risk of malposition and extrusion. Despite the active use of novel, deep dermal ADMs, the clinical outcomes of this new technology has not been well studied. Methods: This is a prospective study to evaluate surgical and patient-reported outcomes using a deep dermal ADM, FlexHD Pliable. Surgical outcomes and BREAST-Q patient-reported outcomes were evaluated postoperatively at 2- and 6-month time points. Results: Seventy-two breasts (41 patients) underwent reconstruction. Complication rate was 12.5%, including 2 hematomas and 7 flap necroses. One case of flap necrosis led to reconstructive failure. Notably, there were no cases of infection, seroma, or implant extrusion or malposition. Average BREAST-Q scores were satisfaction with outcome (70.13 ± 23.87), satisfaction with breasts (58.53 ± 20.00), psychosocial well being (67.97 ± 20.93), sexual well being (54.11 ± 27.72), and physical well being (70.45 ± 15.44). Two-month postoperative BREAST-Q scores decreased compared with baseline and returned to baseline by 6 months. Postoperative radiation therapy had a negative effect on satisfaction with breasts ( P = 0.004) and sexual well being ( P = 0.006). Conclusions: Deep dermal ADM is a novel modification of traditional allograft technology. Use of the deep dermal ADM yielded acceptably low complication rates and satisfactory patient-reported outcomes.